Type of partial edentulousness among patients visiting the department of prosthodontics in a dental college - Pradhan, Dilesh; Adhikari, Ram Kumar (Journal of Kathmandu Medical College, 2022)
Background: There are various combinations of partial edentulism pattern in mandible and maxilla. Documenting the pattern of tooth loss is important for health care planning as it indicates the health of people and satisfaction of oral health care system. Objectives: To find out different types of partial edentulism among patients who come to the Department of Prosthodontics for prosthesis. Methods: A descriptive cross sectional study was carried out in 350 patients at Kathmandu Medical College and Teaching Hospital (KMCTH) visiting Department of Prosthodontics over the period of three months (July 2021 - September 2021) by convenience sampling method with complaint of partial edentulism. Ethical approval for the study was granted by Institutional Review Committee of KMCTH on 8th June 2021. The data obtained were entered and analysed using Statistical Package for Social Sciences (SPSS) v.18. Results: Single most common reason for tooth loss was found to be dental caries (102,29.14 %). Multiple most common reason for tooth loss were dental caries and periodontal disease (117,33.43 %). Partial edentulism in maxillary arch only 112(32%), in mandibular arch only 172(49.14%) and in both arches 66(18.86%). Kennedy’s Class III type of edentulism was most common in both maxillary arch 104 and mandibular arch 157. Conclusion: Kennedy’s Class III is most common type of partial edentulism in both maxillary and mandibular arch. Preventive programs targeted at reducing tooth loss need to be developed and implemented at national level since most prevalent cause of tooth loss is preventable.